Does Electoral Accountability Affect Economic Policy Choices? Evidence from Gubernatorial Term Limits - Besley, T.; Case, A. (Quarterly Journal of Economics, 1995)
This paper analyzes the behavior of U. S. governors from 1950 to 1986 to investigate a reputation-building model of political behavior. We argue that differences in the behavior of governors who face a binding term limit and those who are able to run again provides a source of variation in discount rates that can be used to test a political agency model. We find evidence that taxes, spending, and other policy instruments respond to a binding term limit if a Democrat is in office. The result is a fiscal cycle in term-limit states, which lowers state income when the term limit binds.